The importance of everyday life in anthropological studies (Revista LIDER, 2021)
In this essay, the author shows the relevance of an analitical perspective of everyday life for the anthropological researches. In that way, the author makes a summary about different proposals that have been made during the XXth century and he comments reaches and limitations of the concept of everyday life by the chilean philosopher Humbert Giannini. At the end, the author exempliflies how the everyday life could be relevant for social researches that deal with Justice.